Genetic Variation of Echinococcus canadensis (G7) in Mexico - Rodriguez-Prado, Ulises (Am J Trop Med Hyg, 2014)
We evaluated the genetic variation of Echinococcus G7 strain in larval and adult stages using a fragment of the mitochondrial cox1 gen. Viscera of pigs, bovines, and sheep and fecal samples of dogs were inspected for cystic and canine echinococcosis, respectively; only pigs had hydatid cysts. Bayesian inferences grouped the sequences in an E. canadensis G7 cluster, suggesting that, in Mexico, this strain might be mainly present. Additionally, the population genetic and network analysis showed that E. canadensis in Mexico is very diverse and has probably been introduced several times from different sources. Finally, a scarce genetic differentiation between G6 (camel strain) and G7 (pig strain) populations was identified.